A review of omalizumab for the management of severe asthma - Lin CH; Cheng SL (Dove Medical Press, 2016)
Ching-Hsiung Lin,1–3 Shih-Lung Cheng4,5 1Division of Chest Medicine, Department of Internal Medicine, Changhua Christian Hospital, Changhua, Taiwan, Republic of China; 2Department of Respiratory Care, College of Health Sciences, Chang Jung Christian University, Tainan, Taiwan, Republic of China; 3School of Medicine, Chung Shan Medical University, Taichung, Taiwan, Republic of China; 4Department of Internal Medicine, Far Eastern Memorial Hospital, Taipei, Taiwan, Republic of China; 5Department of Chemical Engineering and Materials Science, Yuan Ze University, Zhongli City, Taoyuan County, Taiwan, Republic of China Abstract: Despite the expansion of the understanding in asthma pathophysiology and the continual advances in disease management, a small subgroup of patients remain partially controlled or refractory to standard treatments. Upon the identification of immunoglobulin E and other inflammatory mediators, investigations and developments of targeted agents have thrived. Omalizumab is a humanized monoclonal antibody that specifically targets the circulating immunoglobulin E, which in turn impedes and reduces subsequent releases of the proinflammatory mediators. In the past decade, omalizumab has been proven to be efficacious and well-tolerated in the treatment of moderate-to-severe asthma in both trials and real-life studies, most notably in reducing exacerbation rates and corticosteroid use. While growing evidence has demonstrated that omalizumab may be potentially beneficial in treating other allergic diseases, its indication remains confined to treating severe allergic asthma and chronic idiopathic urticaria. Future efforts may be focused on determining the optimal length of omalizumab treatment, seeking biomarkers that could better predict treatment response, as well as extending its indications. Keywords: severe asthma, IgE, omalizumab, exacerbation, chronic idiopathic urticarial, inhaled corticosteroid